2021
DOI: 10.3390/cells10071773
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cells Profiling in ANCA-Associated Vasculitis Patients—Relation to Disease Activity

Abstract: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV) are a group of necrotizing multiorgan autoimmune vasculitides that predominantly affect small blood vessels and are associated with the presence of ANCAs. The aim was to assess regulatory and effector cell populations accompanied by the suPAR biomarker level and link the so-defined immune state to the AAV disease activity. The research involved a multicomponent description of an immune state encompassing a range of B and T cell subsets su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…In 2021, Zabinska et al observed a statistically significant correlation between suPAR levels and kidney function in AAV with renal involvement associated with the immune activation state. So, the observed correlation between suPAR and the reported clinical characteristics may suggest that suPAR has the capacity to indicate renal involvement and disease severity [44].…”
Section: Anca-associated Vasculitis (Aav)mentioning
confidence: 96%
See 1 more Smart Citation
“…In 2021, Zabinska et al observed a statistically significant correlation between suPAR levels and kidney function in AAV with renal involvement associated with the immune activation state. So, the observed correlation between suPAR and the reported clinical characteristics may suggest that suPAR has the capacity to indicate renal involvement and disease severity [44].…”
Section: Anca-associated Vasculitis (Aav)mentioning
confidence: 96%
“…The kidney is the most organ susceptible to the disease. MyeloPeroxidase (MPO) and PRoteinase 3 (PR3) are the two most significant target antigens of ANCAs, which are the serologic markers of AAV [44]. SuPAR is linked to kidney disorders and has been used to predict the progression of renal function loss.…”
Section: Anca-associated Vasculitis (Aav)mentioning
confidence: 99%
“…Abnormal activation of B cells was observed in AAV patients and was associated with disease severity or poor outcomes. [ 92 , 93 , 94 ] Clinical trials have shown that depletion of B cells with rituximab is a useful treatment for AAV. [ 41 , 42 ] All evidence suggests that B cells have a vital role in the pathogenesis of AAV.…”
Section: Pathogenesismentioning
confidence: 99%
“…T cells play key roles in a variety of autoimmune diseases ( 239 , 240 , 247 , 250 , 258 , 260 ) and can enter and reside in the epidermis and dermis. Their recirculation between blood, lymphoid organs and other tissues is regulated by the circadian system ( 190 , 382 , 386 ) and by sleep ( 387 , 388 ).…”
Section: Potential Effects Of Shift Work On Skin and Immune Cellsmentioning
confidence: 99%